Characteristics of plant trait network and its influencing factors in impounded lakes and channel rivers of South-to-North Water Transfer Project, China - Zhu, Tianshun; Jiang, Wanxiang; Shen, Henglun; Yuan, Juanjuan; Chen, Jing; Gong, Zheng; Wang, Lihong; Zhang, Meng; Rao, Qingyang (Frontiers in Plant Science, 2023)
Trait-based approaches have been widely used to evaluate the effects of variable environments on submerged macrophytes communities. However, little research focused on the response of submerged macrophytes to variable environmental factors in impounded lakes and channel rivers of water transfer project, especially from a whole plant trait network (PTN) perspective. Here, we conducted a field survey designed to clarify the characteristic of PTN topology among impounded lakes and channel rivers of the East Route of South-to-North Water Transfer Project (ERSNWTP) and to unravel the effects of determining factors on the PTN topology structure. Overall, our results showed that leaf-related traits and organ mass allocation traits were the hub traits of PTNs in impounded lakes and channel rivers of the ERSNWTP, which traits with high variability were more likely to be the hub traits. Moreover, PTNs showed different structures among impounded lakes and channel rivers, and PTNs topologies were related to the mean functional variation coefficients of lakes and channel rivers. Specially, higher mean functional variation coefficients represented tight PTN, and lower mean functional variation coefficients indicated loose PTN. The PTN structure was significantly affected by water total phosphorus and dissolved oxygen. Edge density increased, while average path length decreased with increasing total phosphorus. Edge density and average clustering coefficient showed significant decreases with increasing dissolved oxygen, while average path length and modularity exhibited significant increases with increasing dissolved oxygen. This study explores the changing patterns and determinants of trait networks along environmental gradients to improve our understanding of ecological rules regulating trait correlations.